El tratamiento informativo del medio comunitario Puruhá TV del proceso electoral del 2023 - Hernández Salazar, Karoline Estefania (2025)
This study examines the news programming of the community media outlet Puruhá TV during the 2023 electoral process with the aim of analyzing the structure, content, and quality of its electoral coverage to identify strengths and limitations in its communication policy. For this purpose, a non-experimental, qualitative design was used, based on semi-structured interviews with media operators and analysis of the content broadcast by the television station in its digital formats. The results show that the coverage focused on one-on-one interviews with the candidates, with no space for confrontation between proposals or multiparty debate. The use of unofficial sources and the candidates' statements predominated. Although the messages were explicit, most lacked analytical substance and leaned toward personal campaigns rather than contextual analysis. Similarly, digital platforms were underutilized. Therefore, it is concluded that Puruhá TV's election coverage was biased and limited, with structural, operational, and editorial challenges that must be addressed to strengthen the media's role in future democratic processes.